Recommendation Systems, Parents, and Preschool Children: The Story Behind Digital Technology - Mihelač, Lorena (Revija za elementarno izobraževanje, 2024)
A survey was conducted in November 2023, involving 554 Slovenian parents and their preschool-aged children. The survey aimed to investigate the following: (i) the way parents and their preschool-aged children employ social media and digital technology; (ii) the parents’ comprehension of the term “information bubbles”, and (iii) the parents’ awareness of recommendation systems. Parental and child digital technology patterns and behaviours are correlated, according to the findings. The results suggest that most parents have a restricted understanding of the operational mechanisms of recommendation systems and how they contribute to the construction of “information bubbles.”